Low genome‐wide divergence between two lizard populations with high adaptive phenotypic differentiation. Issue 24 (9th December 2021) - Llanos‐Garrido, Alejandro; Pérez‐Tris, Javier; Díaz, José A.
Abstract: Usually, adaptive phenotypic differentiation is paralleled by genetic divergence between locally adapted populations. However, adaptation can also happen in a scenario of nonsignificant genetic divergence due to intense gene flow and/or recent differentiation. While this phenomenon is rarely published, findings on incipient ecologically driven divergence or isolation by adaptation are relatively common, which could confound our understanding about the frequency at which they actually occur in nature. Here, we explore genome‐wide traces of divergence between two populations of the lacertid lizard Psammodromus algirus separated by a 600 m elevational gradient. These populations seem to be differentially adapted to their environments despite showing low levels of genetic differentiation (according to previously studies of mtDNA and microsatellite data). We performed a search for outliers (i.e., loci subject to selection) trying to identify specific loci with FST statistics significantly higher than those expected on the basis of overall, genome‐wide estimates of genetic divergence. We find that local phenotypic adaptation (in terms of a wide diversity of characters) was not accompanied by genome‐wide differentiation, even when we maximized the chances of unveiling such differentiation at particular loci with FST ‐based outlier detection tests. Instead, our analyses confirmed the lack of genome‐wide differentiation on the basis of more than 70, 000 SNPs, which is concordant with a scenario of local adaptation without isolation by environment. Our results add evidence to previous studies in which local adaptation does not lead to any kind of isolation (or early stages of ecological speciation), but maintains phenotypic divergence despite the lack of a differentiated genomic background. Abstract : Here, we show that local phenotypic adaptation (supported by a wide diversity of characters and previous experimental work) is not accompanied by genome‐wide differentiation, even when we maximized the chances of unveiling such differentiation at particular loci with FST‐based outlier detection tests. We believe in the importance of adding evidence to previous studies in which local adaptation does not lead to any kind of isolation, as ecologically‐driven divergences seem to be dominant in related bibliography.